Generation of 70 fs broadband pulses in a hybrid nonlinear amplification system with mode-locked Yb:YAG ceramic oscillator. (26th October 2017) - Liu, Yang; Wang, Chao; Luo, Daping; Yang, Chao; Li, Jiang; Ge, Lin; Pan, Yubai; Li, Wenxue
Abstract: We demonstrate the passively mode-locked laser performances of bulk Yb:YAG ceramic prepared by non-aqueous tape casting, which generates initial pulses in temporal width of 3 ps and spectrum width of 3 nm without intra-cavity dispersion management. The ceramic laser is further used as seeding oscillator in a fiber nonlinear amplification system, where ultrashort pulses in maximum output power of ∼100 W and pulse duration of 70 fs are achieved. Moreover, the laser spectrum is broadened to be ∼41 nm due to self-phase modulation effects in the gain fiber, overcoming the narrow spectrum limitations of ceramic materials. Our approach opens a new avenue for power-scaling and spectrum-expanding of femtosecond ceramic lasers.